2022
DOI: 10.1021/acscatal.2c05155
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Computational Screening of Metal–Organic Frameworks as High-Performance Electrocatalysts for CO2RR

Abstract: Metal–organic frameworks (MOFs) are considered as promising electrocatalytic materials for the carbon dioxide reduction reaction (CO2RR) due to their various excellent properties. Here, through multistep high-throughput screening of the Computation-Ready, Experimental (CoRE) MOF database, including structural rationality check, pore size screening, adsorption capacity prediction, open metal site identification, CO2 molecular activation capacity, and reaction path calculation, MOFs named GAFRUD, CAJQEL, and cg4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…21 Hai et al found that, for some MOFs, the selectivity of HCOOH depended on the adsorption energy difference between *HCOO and *COOH by DFT calculations. 98 Thus, the biggest obstacle is that HER would severely inhibit eCO 2 RR. 99 Graphite carbonitride (g-C 3 N 4 ) contains unique chemical composition, p-conjugated electronic structure and strong nucleophilic ability.…”
Section: Eco 2 Rr To Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Hai et al found that, for some MOFs, the selectivity of HCOOH depended on the adsorption energy difference between *HCOO and *COOH by DFT calculations. 98 Thus, the biggest obstacle is that HER would severely inhibit eCO 2 RR. 99 Graphite carbonitride (g-C 3 N 4 ) contains unique chemical composition, p-conjugated electronic structure and strong nucleophilic ability.…”
Section: Eco 2 Rr To Acidsmentioning
confidence: 99%
“… 21 Hai et al found that, for some MOFs, the selectivity of HCOOH depended on the adsorption energy difference between *HCOO and *COOH by DFT calculations. 98 Thus, the biggest obstacle is that HER would severely inhibit eCO 2 RR. 99 …”
Section: Electrochemical Conversion Of Comentioning
confidence: 99%
“…Our approach here can be contrasted with multiobjective filtering approaches where hard thresholds are defined for each metric based on prior knowledge to screen materials [31][32][33][34].…”
Section: B Electrocatalyst Discovery As a Multiobjective Problemmentioning
confidence: 99%
“…27 Recently, various MOF candidates were systematically screened through a multiple-step high-throughput screening protocol for high-performance electrocatalysts. 29 Overall, comprehensively regulating the intrinsic activity and the number of accessible active sites in MOFs is expected to break the bottleneck of their electrocatalytic activity, thereby promoting their practical applications.…”
Section: Introductionmentioning
confidence: 99%